C. S. Lewis and the Rejection of the Tao - Greggersen, Gabriele (Dialog, 2003)
When asking about the worldview and ethics behind such stories as The Chronicles of Narnia, readers should try to understand C.S. Lewis's work in light of the Tao or moral Natural Law. Even though our modern culture affirms a relativism in values, Lewis affirms a non-relativist universal ground for moral judgment. Lewis's theological work, Mere Christianity, provides the clue for this interpretation. Despite the apparent negativity or violence in even some of the most memorable scenes in the Chronicles, the underlying moral is hopeful and positive, reflecting a ‘mere Christian’ worldview.